2017
DOI: 10.18632/oncotarget.16071
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte telomere length-related genetic variants in ACYP2 contribute to the risk of esophageal carcinoma in Chinese Han population

Abstract: BackgroundShort leukocyte telomere length has been associated with significantly increased risk of esophageal carcinoma. A previous genome-wide association study demonstrated that ACYP2 was associated with leukocyte telomere length. However, the role of ACYP2 genetic variants on esophageal carcinoma susceptibility is still unknown. Therefore, we investigated whether ACYP2 polymorphisms have impact on the risk of esophageal carcinoma in Chinese.Materials and MethodsWe conducted a case-control study among 386 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…37 Thus, mutations in the ACYP2 gene may modulate apoptosis and promote tumor development. Current studies reported that ACYP2 gene polymorphisms were associated with stroke, 38 lung cancer, 32 esophageal cancer, 39 breast cancer 40 and gastric cancer. 41 In this study, the 'G' allele of rs6713088 in the ACYP2 gene, was distributed in 45.2% of patients with HCC and 39.3% of healthy individuals, revealing a statistically significant association with HCC risk (OR = 1.27, 95% CI = 1.07-1.52, p = 0.007).…”
Section: Acyp2 Gene Polymorphismsmentioning
confidence: 99%
“…37 Thus, mutations in the ACYP2 gene may modulate apoptosis and promote tumor development. Current studies reported that ACYP2 gene polymorphisms were associated with stroke, 38 lung cancer, 32 esophageal cancer, 39 breast cancer 40 and gastric cancer. 41 In this study, the 'G' allele of rs6713088 in the ACYP2 gene, was distributed in 45.2% of patients with HCC and 39.3% of healthy individuals, revealing a statistically significant association with HCC risk (OR = 1.27, 95% CI = 1.07-1.52, p = 0.007).…”
Section: Acyp2 Gene Polymorphismsmentioning
confidence: 99%
“…In contrast to these studies we found that 57% of the patients without audiometrical measured ototoxicity carried the A allele and 43% of the patients with mild to moderate audiometrical measured ototoxicity. A study by Fang et al described an increased risk of esophageal carcinoma associated with the genetic variant rs11125529 in the ACYP2 [27]. Although another variant of the A allele was found and a Chinese population was studied, a genetic variant of the A allele could be related to head and neck cancer and therefore found more often in our cohort.…”
Section: Discussionmentioning
confidence: 65%
“…Our results showed that rs6713088 was significantly associated with an increased risk of RCC. Other studies found that rs6713088 was also associated with increased risk of colorectal cancer (OR = 1.75, 95% CI: 1.03–2.97, p = .038) (Fang et al, ), gastric cancer (OR = 1.30, 95% CI: 1.03–1.64, p = .024) (Li et al, ), and liver cancer (OR = 1.27, 95% CI: 1.07–1.52, p = .007) (Chen et al, ). In addition, rs843711 also exhibited an increased risk of RCC both under the recessive and log‐additive model.…”
Section: Discussionmentioning
confidence: 95%
“…Some studies indicated that the ACYP2 polymorphisms were associated with breast cancer (Liu et al, ; Zhang et al, ), colorectal cancer (Fang et al, ), lung cancer (Chen et al, ), gastric cancer (Li et al, ), and liver cancer (Chen et al, ). However, there are no previous reports examining the role of ACYP2 polymorphisms in the risk of RCC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation